The cay [compact disc, unabridged] - Taylor, Theodore, 1921-2006 (Listening Library, 2005)
When the freighter on which they are traveling is torpedoed by a German submarine during World War II, an adolescent white boy, blinded by a blow on the head, and an old black man are stranded on a tiny Caribbean island where the boy acquires a new kind of vision, courage, and love from his old companion.